Redescription of the sea anemones Anthopleura hermaphroditica and Bunodactis hermafroditica (Cnidaria: Anthozoa: Actiniaria) from Chile - Carlos Spano (Revista de Biología Marina y Oceanografía, 2013)
The Chilean sea anemones Anthopleura hermaphroditica and Bunodactis hermafroditica have been confused repeatedly due to ambiguity in the definition of their diagnostic features. The present article re-describes and compares both species in relation to their synonymic history by examining the external and internal anatomy of several specimens collected between Antofagasta and Chiloé. Although very similar, A. hermaphroditica and B. hermafroditica can be distinguished by the coloration patterns of the oral disc, development of verrucae, presence of zooxanthellae, and the cnidae of the column and the mesenterial fi laments. Based on these differences, the authorship of Bunodactis hermafroditica belongs to Carlgren (1959) but because the type material does not match with the description; we designate a neotype that contains the features identified by this author. While the validity of acrorhagi to differentiate genera is questioned, some amendments to the terminology used in the diagnosis of Anthopleura and Bunodactis are proposed. Hence, we reject the synonymization of the genera Gyractis and Bunodactis, considering the latter as a valid genus until a proper review with the type material of Aulactinia is made. In addition, the remarkable anatomical differences observed among populations of Anthopleura hermaphroditica suggest the presence of at least two distinct species.